Measuring oligopsonistic power in the Kazakh grain processing industry: Empirical evidence from the General Identification Method - Giorgi Chezhia; Oleksandr Perekhozhuk; Thomas Glauben (Journal of New Economy, 2021)
The issues of market structure, pricing behaviour and market power are of great interest to research, industry and society. In recent years, Kazakhstan has become one of the largest wheat producers and exporters on international markets. This paper provides empirical evidence for measuring and identifying oligopsonistic market power in the Kazakh grain processing industry based on the well-known methodological approach in the New Empirical Industrial Organization (NEIO) literature – the General Identification Method (GIM). Using a regional-level panel data set covering the period 2000–2011, two estimation methods, the Nonlinear Three Stage Least Squares (N3SLS) and the Generalized Method of Moments (GMM), were applied to estimate a structural model consisting of a nonlinear system of simultaneous equations. The main result of this empirical analysis is that the market behaviour of Kazakh grain processors in the wheat purchase market is rather competitive. The tests of the market power parameter imply that there was no exercise of oligopsony power. The market power parameter obtained was statistically close to zero, suggesting that grain processors do not have sufficient oligopsonistic market power to influence purchase prices in the Kazakh wheat market during the study period.
Keywords: 630; market power; oligopsony; grain processing industry; New Empirical Industrial Organization (NEIO); General Identification Method (GIM); Kazakhstan